Food and feeding habits of the common eider at Seafield, Edinburgh, in winter - Player, P V (Wildfowl, 1971)
The food and feeding habits of the Common Eider Somateria m. mollissima are described, based on stomach analyses of 50 birds collected between November 1969 and March 1970 from Seafield, Edinburgh. A maximum of 40,000 diving ducks and 2,900 Eiders have been recorded there, attracted by a plentiful food supply and a calm sea. The main foods of the Eiders are molluscs and crustaceans, obtained by diving, up-ending, dipping and scratching out craters. Their feeding cycle is controlled by the time of day and by the tide.